No Interest: The Marginalization of Women in Academic Finance. - Fine, Cordelia; Yadav, Nitin; Murawski, Carsten (Feminist Economics, 2025)
Women experience significant disadvantages within the financial system, and across financial outcomes. This article investigates attention to such issues in academic finance, and its association with authorship gender. Analysis of the authorship of more than 125,000 academic finance articles (1918–2020) reveal persistent dominance of US-based men. The study uses the natural language processing technique of topic modeling to infer topics within a subset of this corpus for which abstracts were available (1988–2020). This reveals gendered patterns of publishing and an absence of attention to group-based inequalities. Hand-coding of these abstracts found that women were overrepresented as authors of the 0.78 percent of articles addressing sex/gender issues. These most commonly examined the instrumental benefits of women for others, and least commonly investigated gender barriers in finance-related domains. Results suggest that women's low representation as authors in academic finance is related to the marginalization of women's interests in knowledge production. HIGHLIGHTS: Academic finance is dominated by male authors from US institutions. This literature marginalizes women's interests, despite men's dominance in finance. The most common gender-related research asks how women could benefit others. Women's authorship is greater on articles that include sex/gender analysis. Women's greater representation could increase knowledge that benefits women. My aunt ... died by a fall from her horse when she was riding out to take the air in Bombay. The news of my legacy reached me one night about the same time that the act was passed that gave votes to women. A solicitor's letter fell into the post-box and when I opened it I found that she had left me five hundred pounds a year for ever. Of the two – the vote and the money – the money, I own, seemed infinitely the more important. (Virginia Woolf, A Room of One's Own 1929)